An experimentally validated computational model for progressive damage analysis of notched oxide/oxide woven ceramic matrix composites. (1st February 2017) - Zhang, Dianyun; Meyer, Pascal; Waas, Anthony M.
Abstract: The focus of this paper is to examine the effect of a notch on the failure response of an oxide/oxide ceramic matrix composite (CMC) subjected to room-temperature tensile loading. The CMC is made of aluminosilicate matrix reinforced by 3M Nextel™ 610 alumina fibers (AS/N610) that are woven into an eight-harness satin weave (8HSW) preform. Uniaxial tensile tests were carried out on both un-notched and single-edge-notched tensile (SENT) specimens of two different lay-ups, ( 0 / 90 ) S and ( 45 / 0 / - 45 / 0 ) S, using a hydraulically activated load frame. The digital image correlation (DIC) technique was utilized to map the deformation histories and identify the locations of strain concentration for both un-notched and SENT specimens. The experimental results were subsequently used to develop a lamina-level constitutive model for a single 8HSW ply that incorporates damage and fracture mechanics implemented through a finite element (FE) framework. A secant-modulus approach was employed to model the pre-peak nonlinear damage evolution, while the post-peak softening was modeled using the smeared crack approach (SCA). Utilizing the ply properties measured from the un-notched ( 0 / 90 ) S and ( 45 / 0 / - 45 / 0 ) S tension tests, the proposed computational model is able to predict the failure strength and strain localization in the SENT specimens. Such a predictive model can aid in the design of CMC structures and accelerate the development of CMCs for engineering applications.